2017
DOI: 10.1155/2017/6139634
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Liquid Biopsy in Targeted Therapy of Metastatic Colorectal Cancer

Abstract: Background. Colorectal cancers (CRC) shed DNA into blood circulation. There is growing evidence that the analysis of circulating tumor DNA can be effectively used for monitoring of disease, to track tumor heterogeneity and to evaluate response to treatment. Case Presentation. Here, we describe two cases of patients with advanced CRC. The first case is about a patient with no available tissue for analysis of RAS mutation status. Liquid biopsy revealed RAS-wild-type and the therapy with anti-EGFR (epidermal grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Some studies identified RAS mutations in ctDNA after anti‐EGFR therapy. A case series indicated that detection of RAS mutations in the plasma during anti‐EGFR therapy provided early warning of impending resistance, which was confirmed several months later by imaging . A retrospective analysis of ctDNA from mCRC patients refractory to anti‐EGFR therapy showed that KRAS codon 61 and 146 mutations were more common than in treatment‐naïve patients and the frequency of acquired KRAS mutations was inversely correlated with the time since last anti‐EGFR therapy .…”
Section: Identification Of Biomarkers Related To Resistance To Epidermentioning
confidence: 97%
“…Some studies identified RAS mutations in ctDNA after anti‐EGFR therapy. A case series indicated that detection of RAS mutations in the plasma during anti‐EGFR therapy provided early warning of impending resistance, which was confirmed several months later by imaging . A retrospective analysis of ctDNA from mCRC patients refractory to anti‐EGFR therapy showed that KRAS codon 61 and 146 mutations were more common than in treatment‐naïve patients and the frequency of acquired KRAS mutations was inversely correlated with the time since last anti‐EGFR therapy .…”
Section: Identification Of Biomarkers Related To Resistance To Epidermentioning
confidence: 97%
“…To personalize EGFR-directed treatment, we need to gain insight into alternative ways to target this essential pathway. This may include the development of liquid biopsy approaches to monitor for resistant subclones (40,41), drug holiday strategies to hamper the selection of RAS-mutant subclones (42), and the development of agents with alternative or multiple epitope recognition that may overcome resistance by acquired EGFR ectodomain mutations or that prevent their selection in the first place (22,43).…”
Section: Discussionmentioning
confidence: 99%
“…This is reasoned by predominant suppression of RAS wild-type clones during anti-EGFR mAb therapy and, in this manner, indirect selection of RAS mutated clones. However, after the discontinuation of EGFR inhibition, RAS mutational load rapidly decreases within a few weeks, probably due to the lack of selective pressure by the anti-EGFR mAb therapy [7] , [15] , [16] , [17] . Supported by data of Santini et al, retreatment (aka rechallenge) with anti-EGFR mAb therapy is currently under active investigation in clinical trials [18] .…”
Section: Discussionmentioning
confidence: 99%